EFFECT OF WEATHER FACTORS ON COCONUT AND COP PRODUCTION IN KERALA, INDIA - K Satyabalan (International Coconut Community, 1997)
Studies made on the constituents of the coconut fruits harvested from West Coast Tall coconut palms grown under rainfed conditions during the different seasons of the year identified as hot weather season from March to May, southwest monsoon season from June to August, North east monsoon season from September to November and cold weather season from December to February in Kerala, India have indicated that the fruits harvested during the hot weather season arc smaller in size but more in number than those harvested during the other seasons of the year. They have low husk content but more kernel content resulting in more copra content per nut. Shell content also is high in these nuts. In the case of fruits harvested during other seasons of the year the number of nuts obtained is low. They are larger in size and have more husk content but less kernel and copra content per nut. The nut characteristics arc very much influenced by the weather conditions prevailing during the twelve month period of development from the fertilized flower to the mature nut. The studies also show that the effects of the season are not operating in the same way or to the same extent on the different constituents of the fruit like husk, kernel, shell and copra. This is evident from the variation in the constituents of the fruit. The data indicate that maximum output of kernel, shell and copra are obtained from the palms during the hot weather season.